Síntesis, caracterización y propiedades catalíticas de nanopartículas de TiO2-Ag/grafeno - Pimentel Guzmán, Thalia Alejandra (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
The textile industry contributes directly to the contamination of water with toxic materials such as methylene blue, rhodamine-B, among others. The synthesis of TiO2-Ag nanoparticles deposited on graphene oxide (TiO2-Ag/GO) can be carried out easily, with low environmental impact and help in the removal of contaminants in wastewater. In the following investigation, TiO2-Ag/GO nanoparticles were prepared. GO films were synthesized using the modified Hummers method. TiO2 nanoparticles were synthesized by a sol-colloidal method. The materials were characterized by means of X-ray diffraction (XRD), scanning electron microscopy (SEM), as well as ultraviolet visible spectroscopy (UV-VIS), and FT-IR. Also, the photocatalytic activity of TiO2-Ag/GO was measured in the removal of contaminants methylene blue (MB) and rhodamine-B (RhB). SEM analysis confirmed the deposition of TiO2-Ag in GO with Dumbell morphology and sizes less than 100 nm. The XRD technique demonstrated the pureness of graphite and the oxidation of GO, as well as the crystal structure of the TiO2-Ag/GO hybrid. FT-IR spectroscopy showed the absorption bands related to graphite, GO, and the Ag/GO, TiO2-Ag/GO hybrids. The Uv-Vis spectroscopy technique corroborated the characteristic absorption bands of the hybrid Ag/GO, showing a band at 410 nm for silver and another at 221 nm for GO. Also with this technique, the measurements of photocatalytic degradation of the contaminants by the composites were carried out, obtaining 95% AM and 88% RhB when using GO, while 99% AM and 98% RhB were obtained using Ag/ GO and finally, 75.6% AM and 98% RhB were obtained using TiO2-Ag/GO. Obtaining the best AM result in Ag/GO and the best RhB result with TiO2-Ag/GO.

La industria textil contribuye de manera directa en la contaminación del agua con materiales tóxicos tales como azul de metileno, rodamina-B, entre otros. La síntesis de las nanopartículas de TiO2-Ag depositadas en óxido de grafeno (TiO2-Ag/GO) puede efectuarse fácilmente, con un bajo impacto ambiental y ayudar en la eliminación de contaminantes en aguas residuales. En esta investigación se prepararon nanopartículas de TiO2-Ag/GO. Las películas de GO fueron sintetizadas a través del método Hummers modificado. Las nanopartículas de TiO2 se sintetizaron mediante un método sol-coloidal. Los materiales se caracterizaron por medio de las técnicas de difracción de rayos-X (DRX), microscopía electrónica de barrido (MEB), así como por las espectroscopías ultravioleta visible (UV-VIS), y FT- IR. También se midió la actividad fotocatalítica del TiO2-Ag/GO, en la remoción de los contaminantes azul de metileno (AM) y rodamina-B (RhB). El análisis de MEB confirmó la depositación de TiO2-Ag en GO con morfología Dumbell y tamaños inferiores a 100 nm. La técnica de DRX, demostró la pureza del grafito y la oxidación del GO, así como la estructura cristalina del híbrido TiO2-Ag/GO. La espectroscopía FT-IR mostró las bandas de absorción relacionadas con el grafito, GO, y los híbridos Ag/GO, TiO2-Ag/GO. La técnica de espectroscopía Uv-Vis corroboró las bandas de absorción características del híbrido Ag/GO, mostrando una banda en 410 nm para la plata y otra en 221 nm para el GO. También con dicha técnica se realizaron las mediciones de degradación fotocatalítica de los contaminantes por los compósitos, obteniéndose 95% de AM y 88% de RhB al emplear GO, mientras que, se obtuvo un 99% de AM y 98% de RhB usando Ag/GO y finalmente, se obtuvo un 75.6% de AM y 98% de RhB usando TiO2-Ag/GO. Obteniendo el mejor resultado de AM en Ag/GO y el mejor resultado de RhB con TiO2-Ag/GO.
Instituto de Investigación en Metalurgia y Materiales. Maestría en Metalurgia y Ciencias de los Materiales
Keywords: info:eu-repo/classification/cti/7; IIMM-M-2022-0958; Nanopartículas huecas; Anatasa; Fotocatálisis; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/8458